STRATEGI PENDIDIKAN KARAKTER MELALUI LAYANAN BIMBINGAN DAN KONSELING DI SMP NEGERI 1 PLOSO JOMBANG - Mohammad Ridho; Cep Ridhwan; Arif Khunaifi; Moh Slamet; Suhari (Menara Tebuireng, 2021)
This study discusses the focus on (1) how Strategy character education students through guidance and counseling services in SMP Negeri 1 Jombang Ploso. (2) how is the implementation of character education students through guidance and counseling services in SMP Negeri 1 Jombang Ploso.This study uses a qualitative method, which is to describe and interpret data that has been obtained so that it will represent reality in accordance with existing phenomena. For methods of collecting data in this study use three techniques: (1) observation, (2) interviews (3) method of documentation data obtained from reports and documents. These findings resulted in two findings: first, strategy character education students through guidance and counseling services in SMP Negeri 1 Jombang Ploso are as follows: a. religious development activities, b. development of extra-curricular activities, c. modeling / sample, d. environment conditioning activities, e. routine activities, f. social activities, g. reprimand. Second, implementation of character education in the country SMP Negeri 1 Ploso is: a. integration character education in the subjects, b. through local content subjects, c. through religious activity, d. self-development / extracurricular activities.